2002
DOI: 10.1164/rccm.20110-040oc
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vascular Endothelial Growth Factor in Sleep Apnea Syndrome

Abstract: Sleep apnea syndrome is associated with recurrent episodic hypoxia during sleep, which has been implicated in the development of cardiovascular morbidity. Hypoxia is the major stimulus of vascular endothelial growth factor (VEGF), which is a potent angiogenic cytokine. In the present article we describe the results of three experiments in which plasma concentrations of VEGF were measured in patients with sleep apnea. In Experiment 1, apnea-hypopnea index was found to be a significant independent predictor of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(47 citation statements)
references
References 43 publications
7
33
1
6
Order By: Relevance
“…In addition, VEGF concentrations fall in response to reversal of OSA by CPAP. 58,59 As of yet, however, there is no direct evidence of enhanced VEGF-induced angiogenesis in OSA. Nevertheless, variations in the VEGF response to nocturnal hypoxia may influence the cardiovascular system's response to tissue hypoxia.…”
Section: Bradley and Florasmentioning
confidence: 99%
“…In addition, VEGF concentrations fall in response to reversal of OSA by CPAP. 58,59 As of yet, however, there is no direct evidence of enhanced VEGF-induced angiogenesis in OSA. Nevertheless, variations in the VEGF response to nocturnal hypoxia may influence the cardiovascular system's response to tissue hypoxia.…”
Section: Bradley and Florasmentioning
confidence: 99%
“…A possible mechanism is thought to be secondary to hypoxemia-induced endothelial cell dysfunction and pulmonary artery remodeling [81]. This may be related to hypoxia upregulation vascular endothelial growth factor, which is a mediator in angiogenesis, resulting in vascular remodeling [82, 83]. Most experts feel that OSA may modestly increase pulmonary arterial pressures, and evaluation for OSA should be part of the initial work-up in patients with pulmonary hypertension [84].…”
Section: Right Ventricle Pulmonary Hypertension and Osamentioning
confidence: 99%
“…The synthesis of VEGF is stimulated by hypoxia-inducible factor 1α and by other GF such as platelet-derived GF, transforming GF α and ÎČ, insulin GF, fibroblast GF and keratinocyte GF [12]. Recent studies have reported high VEGF levels in patients with the sleep apnea syndrome, which decrease after treatment with continuous positive airway pressure [13, 14]. However, others did not find an association [15,16,17] or found that this was not a true association because of the presence of thrombocytosis in OSAS [18], which increases the VEGF level due to a high content of VEGF in platelets [19, 20].…”
Section: Introductionmentioning
confidence: 99%